Keistimewan Bahasa Arab Sebagai Bahasa Al-Qur’an - Nurul Fadillah; Bella Azahra; Sapri Sapri; Fitri Ana Daulay; Miftah Hayati Manjuntak; Nur Adilla; Army Fahita Harahap; Tasya Sabrina (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to examine the special characteristics of Arabic as the language of the Koran. The data collection used in this research is a literature study method and examines in more depth and analyzes articles and books that are relevant and related to the discussion material. The results of the research show that Arabic is a language that is very widely used among Muslims because of its specialty in being used as the language of the Koran. This research also explains that studying Arabic in MI/SD education must be implemented so that students are able to easily study, understand and read the Al-Qur'an properly and correctly. This research provides information about how important the Al-Qur'an is in learning Arabic and vice versa. Because the Al-Qur'an is the main benchmark in making Arabic a center of study among Muslims.